Explanation through functionalism - Moiraghi, F (2020)
The notion of explanation has been widely used to determine and single out dependencies within the Philosophy of Science. In particular, it is often believed that symmetries have a certain priority over laws on the basis of their explanatory role [E.g. Wigner 1964] or that one of the criteria that are employed to discriminate between laws and accidental generalisations is that laws are supposed to "explain" their instances (E.g. Bird 1998). These stances can lead to different hierarchical proposals, sometimes merely methodological but often with strong metaphysical outcomes.